1994
DOI: 10.1029/94rs01162
|View full text |Cite
|
Sign up to set email alerts
|

Study of measured and predicted reliability of the ionospheric HF communication channel at high latitudes

Abstract: This paper describes observations of the reliability of the ionospheric HF communication channel within and close to the northern auroral zone. Automatic equipment has been developed to measure reliability and virtual reflection height as a function of frequency in an hourly cycle. Measurements have been made over two propagation paths within Norway. The data show diurnal and seasonal variations as well as dependence of the measured parameters on geomagnetic conditions. The observations have been compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…All models roughly reproduce the general diurnal trend observed in the measurements during the winter and equinox periods. This observation is consistent with the results of Thrane et al [] in their comparison of measured and modeled reliability and MUF at high latitudes. Both predictions and observations show diurnal and seasonal variations; however, the models do not reproduce the actual hourly variability observed in the measurements.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…All models roughly reproduce the general diurnal trend observed in the measurements during the winter and equinox periods. This observation is consistent with the results of Thrane et al [] in their comparison of measured and modeled reliability and MUF at high latitudes. Both predictions and observations show diurnal and seasonal variations; however, the models do not reproduce the actual hourly variability observed in the measurements.…”
Section: Discussionsupporting
confidence: 93%
“…In Figure a, ICEPAC and VOACAP systematically overestimate the MUF(3000)F2 throughout all the hours, while REC533 gives values close to observations except from 07:00–08:00 UT and 19:00–24:00 UT where small divergences occur. Overestimation in VOACAP and ICEPAC MUF predictions have been observed at high latitudes [e.g., Thrane et al , ; Goodman and Ballard , ]. Thrane et al [] observed a tendency of VOACAP and ICEPAC predictions to overestimate MUF up to a factor of 2 at noon time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations